Assessing the risk of transfusion‐transmitted emerging infectious diseases. (June 2016) - Custer, B.
Abstract : Background: Emerging infectious diseases (EIDs) remain a source of significant concern in blood safety. Methods: Emerging infectious diseases of concern will be described and methods used to conduct risk assessment will be reviewed, with a focus on transfusion medicine. The issues that make EIDs more challenging for blood safety compared to other areas of public health will be demonstrated through specific examples. Results: Current EIDs include mosquito‐borne infections such as dengue, chikungunya and Zika virus. In addition, tick‐borne infections such as Babesia, Borrelia, Anaplasma and Severe Fever with Thrombocytopenia Syndrome Virus (SFTSV) are or have the potential to become significant EIDs in transfusion. Other zoonoses, such as HEV, are expected to emerge or re‐emerge. Often in risk assessment, assumptions are made that transfusion‐transmitted (TT) infection will have the same progression as infection transmitted in other ways. Even with explosive mosquito‐borne epidemics of chikungunya virus, no evidence of TT has been documented. Substantial TT of dengue virus can occur, but significant clinical outcome differences between recipients of dengue RNA(+) and RNA(−) transfusions have not been found. In contrast, while TT of Babesia microti in the USA is a clear threat, there is no consensus on appropriate risk mitigation. Summary: Generalizations from one route of transmission to another and from one pathogen to another may be appropriate for precaution, but may lead to ineffective and cost‐ineffective policies. For risk assessment and blood safety policy to be evidence based, studies of the consequences to blood recipients need to be conducted.